Perceptions and influences of literature on psychological processes and dispositions in contemporary society - Petrović, Nebojša (Psihološka istraživanja, 2024)
Although both literature and psychology study human nature, they are very rarely interdisciplinary connected. The reasons for this lie in their different theoretical focuses and methodological approaches. This paper aims to point out that efforts to bring these complementary approaches to related topics closer together could be beneficial for both disciplines. Recently, there has been a lot of work done globally on intensifying this cooperation. Literary works, through narration, explore motives, feelings, thoughts, and desires, analyzing the inner world of characters, deeper layers of their personality, and inner dilemmas - all of which psychology also deals with by studying real people and trying to understand their behavior. Furthermore, in the reading process, literature can be understood as a simulation of reality to encourage readers to better understand themselves and others, thus achieving a more meaningful life with fewer conflicts. The connection between literary works and their effects on readers is mediated by a series of psychological traits such as openness, immersion, values, or motivation. Literary works, especially in times of great social upheaval, as has been the case in Serbia over the past 30 years, can be a platform for profound and substantive discussions on issues such as the importance of social identities. Contemporary literature, in Serbia, very diverse in topics and approaches, will remain a significant part of the culture of our time. The potential of psychologists in encouraging people to better understand themselves through literature and achieve more benefits is far greater than it currently seems.